Consumer Rights Protection on Sugar Content Information in Ready-to-Eat Food Products: An Analysis of Consumer Protection Law and Health Government Regulation Implementation - Venia Utami Keliat; Anggada Perkasa (jurnal.unprimdn.ac.id, 2025)
The increasing prevalence of non-communicable diseases in Indonesia, particularly diabetes and obesity, correlates with excessive sugar consumption. Ready-to-eat food products often lack comprehensive sugar content information, potentially violating consumer rights. This study analyzes consumer rights protection implementation regarding sugar content information on ready-to-eat food products under Indonesian Consumer Protection Law and Health Government Regulations. This normative legal research employs statutory, case, and comparative approaches. Data were collected through literature review of primary legal sources and secondary materials, analyzed using qualitative descriptive methods. Significant implementation gaps exist despite comprehensive legal frameworks. Only 37% of surveyed outlets provide complete nutritional information. While Article 4(c) of Consumer Protection Law guarantees information rights and PP 28/2021 mandates nutrition labeling, enforcement remains weak. Key obstacles include regulatory inconsistencies, limited institutional capacity, high compliance costs, and low consumer literacy (42% urban, 18% rural). Substantial gaps between legal mandates and actual practice require multi-faceted solutions: regulatory harmonization, institutional strengthening, economic incentives, and massive public education campaigns.